Given the equation:
![(1)/(2)y=8x+3](https://img.qammunity.org/2023/formulas/mathematics/college/arrnqa19vgn1n1uf5w0bk3n9uni1puhmut.png)
Rewrite the equation in slope intercept form:
y = mx + b
Multiply both through by 2
![\begin{gathered} (1)/(2)y\ast2=\text{ }8x\ast2\text{ + 3}\ast2 \\ \\ y\text{ = 16x + 6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qust8c0re76zjsbpv19ijpqy8vsvpola5g.png)
The slope of this line is 16.
therefore, the slope of the line perperndicular to it will be it's inverse:
![-(1)/(16)](https://img.qammunity.org/2023/formulas/mathematics/college/m1rlxrs9v6pqom4poorrhtgjyelhmk5iw6.png)
The perpendicular line has the points:
(x, y) ===> (-8, 0)
We have:
y = mx + b
![0\text{ =-}(1)/(16)(-8)+b](https://img.qammunity.org/2023/formulas/mathematics/college/fi3hbazoamepj1mvay7nsi6cz7uu7su2t6.png)
Solve for b which is the y-intercept:
![\begin{gathered} 0\text{ = }(1)/(2)+b \\ \\ b\text{ = -}(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6a3stokrjuva91xb79ekgn5ru7rs56fz2u.png)
Since the y intercept is -½
slope = -1/16
The equation of the line in point slope form:
(y - y1) = m(x - x1)
![(y\text{ - 0) = -}(1)/(16)(x\text{ + 8)}](https://img.qammunity.org/2023/formulas/mathematics/college/qalg9gspwo0jf97n3mudla1dkmzhpwn5tk.png)
Therefore, the equation of the perpendicular line in slope intercept is:
![y\text{ = -}(1)/(16)x\text{ - }(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/ncbyptovxhco2aarfogoj5c86mycbh8mbr.png)